KAJIAN SOSIAL MENGENAI REALITAS DAN TOLERANSI ANTARUMAT BERGAMA DI KOTA KUPANG PROVINSI NUSA TENGGARA TIMUR - Jelahut, Yosef Emanuel; Jehamat, Lasarus; Pellu, Susana C.L; Perangin Angin, Imanta I; Jelahut, Felisianus Efrem (Jurnal Dakwah Tabligh, 2022)
This study aims to analyze the social reality of tolerance in inter-religious life in Kupang City as well as to explain and analyze the various solutions that can be offered to erode and build a more authentic tolerance. The research method used is a qualitative research method with a descriptive approach. The results of the study show that 1) The inter-religious life in Kupang City is characterized by the phenomenon of pseudo-tolerance. This is indicated by the high level of tolerance ideally at the elite data level, but in religious practice cases of intolerance are still found, 2) There is a spirit to maintain and maintain unity in the field of religion and society. This is marked by the existence of various kinds of togetherness movements in the practice of practicing religion and maintaining unity in the midst of the plurality of the people of Kupang City, 3) Minorities seem to inhabit various kinds of social practices which are discriminatory not only ethnically but also religiously